Tech-Driven Sensory Marketing: Integrating AR/VR, IoT, and OVR to Decode Consumer Emotions - Matloob, Afsha; Das, Ananya; Hota, Sweta Leena; Clement, Sunday (International Journal of Online and Biomedical Engineering (iJOE), 2026)
The tendency to use sensory marketing in business innovation has increased exponentially with advancements in mobile and innovative technologies. The concept of sensory marketing has become widely popular among global marketers to connect with consumers emotionally. Sensory marketing employs the five fundamental senses—taste, smell, touch, vision, and sound—to provide consumers with a distinctive sensory experience. Several technologies, such as haptic technology used in smart mobile phones and olfactory virtual reality (OVR), increase the effectiveness of sensory marketing. It enhances their purchasing behavior by providing them with an effective overview of the products and offerings. Several globally popular brands are currently using this marketing strategy, which can be overwhelming without knowledge of its proper application. Hence, the connection between sensory stimulation, usage of technology, and emotional connection of brands to consumers has been explored through this study.